Paraffin-based phase change energy storage building material as well as preparation method and application thereof

Through the design of paraffin-based phase change energy storage materials, combined with porous matrix materials such as ceramics and expanded perlite, and using styrene acrylic emulsion and epoxy resin to encapsulate, the problems of poor durability and high cost of existing phase change energy storage materials are solved. It achieves efficient heat storage and release, improving the energy utilization efficiency and living comfort of the building.

CN119306416AInactive Publication Date: 2025-01-14LUZHOU VOCATIONAL & TECHN COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411487597.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing phase change energy storage materials have problems such as poor durability, high cost and low energy storage efficiency in construction applications, and physical properties may deteriorate and leak during the thermal cycle, resulting in a reduced heat storage effect.

Method used

Using paraffin-based phase change energy storage materials, encapsulated using styrofoam, stearic acid and polyethylene glycol (PEG 1000) by combining organic paraffin, expanded perlite and expanded clay materials, and encapsulated using styrene acrylic emulsion and epoxy resin , form composite phase change material particles to improve the durability and thermal conductivity of the material.

Benefits of technology

It achieves high energy storage, excellent durability and economy, effectively prevents leakage and physical properties of phase change materials, and improves the energy utilization efficiency and living comfort of the building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306416A_ABST
    Figure CN119306416A_ABST
Patent Text Reader

Abstract

The invention discloses a paraffin-based phase change energy storage building material as well as a preparation method and application thereof. The building material is composed of composite phase change material particles and comprises a phase change material group (organic paraffin, stearic acid and polyethylene glycol), a porous matrix material group (ceramsite, expanded perlite and an expanded clay material) and a packaging material group (styrene-acrylic emulsion and epoxy resin). The preparation method comprises the following steps: preparing raw materials, heating and mixing the phase change material, and drying the porous matrix material; mixing the materials, adsorbing the phase change material into the porous matrix material through a vacuum adsorption method, and packaging with a packaging material; and molding and curing: pouring the mixed material into a mold for molding, and curing at a controlled temperature. The material is uniformly doped into mortar or concrete for buildings, the internal temperature of the buildings is effectively adjusted, the energy consumption is reduced, the living comfort is improved by absorbing and releasing heat, and the material has a remarkable energy-saving effect and excellent durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building energy-saving materials, and in particular to a paraffin-based phase-change energy storage building material and a preparation method and application thereof. Background Art

[0002] As the global energy crisis and environmental pollution become increasingly serious, the development of building energy-saving technology has become the focus of attention of all countries. Phase change energy storage building materials have gradually gained attention because they can absorb or release a large amount of heat during the phase change process, thereby effectively regulating indoor temperature fluctuations and improving the energy efficiency of buildings. However, the phase change energy storage materials currently used in the construction field have problems in durability, economy and energy storage.

[0003] Phase change materials may experience physical property degradation during thermal cycles, and thermal storage materials may leak, resulting in reduced thermal storage effects. In addition, after the materials are combined with the matrix material, the internal pressure may damage the matrix structure. These problems restrict the widespread application of phase change energy storage building materials.

[0004] To this end, we propose a paraffin-based phase change energy storage building material and its preparation method and application. Summary of the invention

[0005] The purpose of the present invention is to provide a paraffin-based phase change energy storage building material and a preparation method and application thereof, which has the advantages of high energy storage, excellent durability and economy, and solves the problems of poor durability, high cost and low energy storage efficiency of existing phase change energy storage materials in building applications.

[0006] To achieve the above object, the present invention provides the following technical solution: a paraffin-based phase change energy storage building material, which is composed of composite phase change material particles, and the material is composed of the following components:

[0007] Phase change material group: organic paraffin, stearic acid, polyethylene glycol (PEG 1000);

[0008] Porous matrix material group: ceramsite, expanded perlite, expanded clay materials;

[0009] Packaging material group: styrene acrylic emulsion, epoxy resin.

[0010] Preferably, the paraffin-based phase change energy storage building material includes the following specific components:

[0011] Organic paraffin: 30-50 parts;

[0012] Stearic acid: 10-20 parts;

[0013] Polyethylene glycol (PEG 1000): 10-20 parts;

[0014] Ceramic granules: 10-30 parts;

[0015] Expanded perlite: 10-30 parts;

[0016] Expanded clay material: 10-20 parts;

[0017] Styrene acrylic emulsion: 5-15 parts;

[0018] Epoxy resin: 5-15 parts.

[0019] Preferably, the specific composition of the paraffin-based phase change energy storage building material is:

[0020] Organic paraffin: 40 parts;

[0021] Stearic acid: 15 parts;

[0022] Polyethylene glycol (PEG 1000): 15 parts;

[0023] Ceramic granules: 20 parts;

[0024] Expanded perlite: 20 parts;

[0025] Expanded clay material: 15 parts;

[0026] Styrene acrylic emulsion: 10 parts;

[0027] Epoxy resin: 10 parts.

[0028] Preferably, the particle size range of the ceramsite and expanded perlite is 1-5 mm;

[0029] The encapsulated composite phase change material particles have a specific surface area of ​​20-40m 2 / g;

[0030] The thermal conductivity of the composite phase change material particles is 0.5-1.5 W / (m·K) in the range of 20-30°C;

[0031] The heat-resistant temperature of the packaging material group is 70-90°C.

[0032] A method for preparing a paraffin-based phase-change energy storage building material comprises the following steps:

[0033] S1. Raw material preparation:

[0034] a) heating the organic paraffin, stearic acid and polyethylene glycol (PEG 1000) to 60-80° C. under stirring until they are completely mixed to form a uniform liquid composite material;

[0035] b) drying the ceramsite, expanded perlite and expanded clay materials at a drying temperature of 100-120° C. for 1-2 hours to reduce the moisture content;

[0036] S2. Material mixing:

[0037] a) mixing the pretreated liquid composite material with the dried ceramsite, expanded perlite and expanded clay material in the proportions to ensure uniform distribution of the components;

[0038] b) During the mixing process, gradually add the styrene acrylic emulsion and epoxy resin and continue stirring for 15-20 minutes to ensure that the mixture is uniform;

[0039] S3, molding and curing:

[0040] a) pouring the mixed material into a mold for molding;

[0041] b) Curing in a controlled temperature environment of 25-35°C for 24-48 hours to ensure the stability and performance of the material.

[0042] Preferably, the S1 raw material preparation step further includes the following specific steps:

[0043] S1.1 Mix organic paraffin, stearic acid and polyethylene glycol (PEG 1000) in proportion, heat until completely melted, and form a uniform phase change material mixture;

[0044] S1.2 Pre-treat the ceramsite and expanded perlite to ensure they are clean and dry;

[0045] S1.3 Use vacuum adsorption to adsorb the phase change material mixture into the interior of ceramsite and expanded perlite.

[0046] Preferably, the S2 material mixing step further includes the following specific steps:

[0047] S2.1 Take 10 parts of styrene acrylic emulsion and 10 parts of epoxy resin by weight and place them in different containers;

[0048] S2.2 Heat the epoxy resin to 60-70°C to reduce its viscosity and facilitate mixing;

[0049] S2.3 Slowly add the heated epoxy resin into the styrene acrylic emulsion while stirring continuously to ensure that the two are evenly mixed;

[0050] S2.4 Continue stirring for 30 minutes to ensure that the mixture is evenly distributed;

[0051] S2.5 allowing the mixed packaging material to stand and cool at room temperature to obtain a final packaging material;

[0052] S2.6 Store packaging materials in airtight containers to protect them from air and moisture.

[0053] Preferably, the S3 molding and curing step further includes the following specific steps:

[0054] S3.1 Mix styrene acrylic emulsion and epoxy resin in proportion to form a packaging material;

[0055] S3.2 Encapsulating the ceramsite and expanded perlite adsorbed with the phase change material with an encapsulation material to form composite phase change material particles;

[0056] S3.3 Add the composite phase change material particles into common building materials, mix them evenly, and prepare phase change energy storage mortar or phase change concrete;

[0057] S3.4 Pour the mixed building materials into a mold, shape and solidify them to obtain the final phase change energy storage building materials.

[0058] An application of a paraffin-based phase change energy storage building material comprises the following steps:

[0059] a) uniformly adding the prepared paraffin-based phase change energy storage building material into building mortar or concrete to ensure uniform distribution of the material;

[0060] b) Pour the mixed mortar or concrete into the prepared mold and shape it as required;

[0061] c) Carry out preliminary curing on the formed building materials, control the temperature at 25-35°C, and the curing time is 24-48 hours to ensure the initial hardening and stable performance of the materials;

[0062] d) The building materials after the initial curing are removed from the mold and subjected to secondary curing in an environment with controlled temperature and humidity for 7-14 days to ensure the final performance of the materials;

[0063] e) Apply the well-maintained phase change energy storage building materials to building structures, and use their energy storage characteristics to improve the thermal environment and energy efficiency of the building.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] 1. The present invention uses cheap and environmentally friendly organic paraffin as a phase change energy storage material, combines stearic acid and polyethylene glycol (PEG 1000) to adjust the phase change temperature and latent heat, thereby achieving the effect of reducing costs and improving energy storage efficiency.

[0066] 2. The phase change material is adsorbed into the porous matrix material (ceramsite, expanded perlite, expanded clay material) by vacuum adsorption method, and encapsulated by styrene acrylic emulsion and epoxy resin to effectively prevent the leakage and physical property degradation of the phase change material and improve the durability of the material.

[0067] 3. By optimizing the ratio and packaging technology of composite phase change materials, the prepared composite phase change material particles have a high specific surface area and excellent thermal conductivity, ensuring the stability and efficiency of energy storage building materials during use.

[0068] 4. Add composite phase change materials to building mortar or concrete and apply them to building structures. Combined with numerical simulation software, thermal performance analysis and optimization can achieve effective regulation of the internal temperature of the building, improve living comfort and building energy saving effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 This is a schematic diagram of the components of the paraffin-based phase-change energy storage building material of the present invention;

[0070] Figure 2 A schematic diagram of the specific components and proportions of the paraffin-based phase-change energy storage building material of the present invention;

[0071] Figure 3 A schematic diagram of the physical properties of the paraffin-based phase-change energy storage building material of the present invention;

[0072] Figure 4 This is a flow chart of the steps of the preparation method of the paraffin-based phase change energy storage building material of the present invention;

[0073] Figure 5 Detailed flow chart of the raw material preparation steps of the present invention;

[0074] Figure 6 It is a detailed flow chart of the material mixing steps of the present invention;

[0075] Figure 7 It is a detailed schematic diagram of the molding and curing steps of the present invention;

[0076] Figure 8 It is a schematic diagram of the application steps of the paraffin-based phase change energy storage building material of the present invention. DETAILED DESCRIPTION

[0077] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0078] See also Figures 1 to 8The present invention provides a technical solution: a paraffin-based phase change energy storage building material, which is composed of composite phase change material particles, and the material is composed of the following components: phase change material group: organic paraffin, stearic acid, polyethylene glycol (PEG 1000); porous matrix material group: ceramsite, expanded perlite, expanded clay material; packaging material group: styrene acrylic emulsion, epoxy resin;

[0079] The paraffin-based phase change energy storage building material of the present invention adopts composite phase change material particles, which are composed of phase change material, porous matrix material and packaging material. The phase change material group includes organic paraffin, stearic acid and polyethylene glycol (PEG1000), which are responsible for absorbing or releasing heat during the phase change process, thereby regulating the temperature inside the building. The porous matrix material group is composed of ceramsite, expanded perlite and expanded clay materials. These porous materials serve as carriers of phase change materials and can effectively separate and encapsulate the phase change materials to prevent leakage. The packaging material group includes styrene acrylic emulsion and epoxy resin, which are used to seal the phase change material to further improve its durability and stability;

[0080] The paraffin-based phase change energy storage building material includes the following specific components: organic paraffin: 30-50 parts; stearic acid: 10-20 parts; polyethylene glycol (PEG 1000): 10-20 parts; ceramsite: 10-30 parts; expanded perlite: 10-30 parts; expanded clay material: 10-20 parts; styrene acrylic emulsion: 5-15 parts; epoxy resin: 5-15 parts.

[0081] These ranges ensure flexibility in formulation of the materials, which can be adjusted according to actual needs. For example, the proportion of organic paraffin is 30-50 parts, which ensures that the material has sufficient heat capacity during the phase change process. Stearic acid and polyethylene glycol (PEG 1000) are 10-20 parts respectively. Their addition can adjust the phase change temperature and latent heat and improve the energy storage performance of the material. The ceramsite, expanded perlite and expanded clay materials in the porous matrix material group are 10-30 parts and 10-20 parts respectively, which provide excellent support structure and adsorption performance. The styrene acrylic emulsion and epoxy resin in the encapsulation material group are 5-15 parts respectively, which ensure the encapsulation effect and durability of the material.

[0082] The particle size range of the ceramsite and expanded perlite is 1-5 mm;

[0083] The encapsulated composite phase change material particles have a specific surface area of ​​20-40m 2 / g;

[0084] The thermal conductivity of the composite phase change material particles is 0.5-1.5 W / (m·K) in the range of 20-30°C;

[0085] The heat-resistant temperature of the packaging material group is 70-90°C.

[0086] The particle size range of ceramsite and expanded perlite is 1-5 mm, which ensures the best physical properties and adsorption effect of the material. The encapsulated composite phase change material particles have a specific surface area of ​​20-40m 2 / g, which means that the particle surface can more effectively exchange heat with the surrounding environment. The thermal conductivity of the composite phase change material particles is 0.5-1.5W / (m·K) in the range of 20-30℃, ensuring that the material has good thermal conductivity during the phase change process. The heat-resistant temperature of the packaging material group is 70-90℃, ensuring the stability and durability of the material in high temperature environments.

[0087] The paraffin-based phase-change energy storage building material of the present invention adjusts the internal temperature of the building by utilizing the heat absorption and heat release characteristics of organic paraffin during the phase change process. When the ambient temperature rises to the melting point of paraffin, the paraffin absorbs heat and melts, thereby lowering the temperature of the surrounding environment. When the ambient temperature drops to the solidification point of paraffin, the paraffin releases heat and solidifies, thereby increasing the temperature of the surrounding environment. In this way, the paraffin-based phase-change energy storage building material can effectively adjust the indoor temperature, reduce the energy consumption of air conditioning and heating systems, and improve the energy efficiency of buildings.

[0088] A method for preparing a paraffin-based phase-change energy storage building material comprises the following steps:

[0089] S1. Raw material preparation:

[0090] a) heating the organic paraffin, stearic acid and polyethylene glycol (PEG 1000) to 60-80° C. under stirring until they are completely mixed to form a uniform liquid composite material;

[0091] b) drying the ceramsite, expanded perlite and expanded clay materials at a drying temperature of 100-120° C. for 1-2 hours to reduce the moisture content;

[0092] S2. Material mixing:

[0093] a) mixing the pretreated liquid composite material with the dried ceramsite, expanded perlite and expanded clay material in the proportions to ensure uniform distribution of the components;

[0094] b) During the mixing process, gradually add the styrene acrylic emulsion and epoxy resin and continue stirring for 15-20 minutes to ensure that the mixture is uniform;

[0095] S3, molding and curing:

[0096] a) pouring the mixed material into a mold for molding;

[0097] b) Curing in a controlled temperature environment of 25-35°C for 24-48 hours to ensure the stability and performance of the material.

[0098] The preparation method includes three main steps: raw material preparation, material mixing, and molding and curing. First, in the raw material preparation step, organic paraffin, stearic acid and polyethylene glycol (PEG 1000) are heated and stirred at a temperature of 60-80°C until a uniform liquid composite material is formed. This process ensures the consistency and performance of the phase change material in subsequent steps. Then, the ceramsite, expanded perlite and expanded clay materials are dried at a temperature of 100-120°C for 1-2 hours to reduce their moisture content to ensure that no excess moisture is introduced in the subsequent material mixing step.

[0099] In the material mixing step, the pre-treated liquid composite material is mixed with the dried ceramsite, expanded perlite and expanded clay materials in proportion to ensure that the components are evenly distributed. Subsequently, styrene acrylic emulsion and epoxy resin are gradually added and stirred for 15-20 minutes to ensure the uniformity of the mixture. Finally, in the molding and curing step, the mixed material is poured into the mold for molding and cured for 24-48 hours in an environment of 25-35°C to ensure the stability and performance of the material.

[0100] The S1 raw material preparation step also includes the following specific steps:

[0101] S1.1 Mix organic paraffin, stearic acid and polyethylene glycol (PEG 1000) in proportion, heat until completely melted, and form a uniform phase change material mixture;

[0102] S1.2 Pre-treat the ceramsite and expanded perlite to ensure they are clean and dry;

[0103] S1.3 Use vacuum adsorption to adsorb the phase change material mixture into the interior of ceramsite and expanded perlite.

[0104] The raw material preparation steps are further refined. First, organic paraffin, stearic acid and polyethylene glycol (PEG 1000) are mixed in proportion and heated to a completely molten state to form a uniform phase change material mixture. This ensures the consistency of the phase change material in subsequent steps. Then, the ceramsite and expanded perlite are pretreated to ensure that they are clean and dry, which helps to improve the adsorption performance of the material. Finally, the phase change material mixture is adsorbed into the interior of the ceramsite and expanded perlite using a vacuum adsorption method, which ensures that the phase change material will not leak during use.

[0105] The S2 material mixing step also includes the following specific steps:

[0106] S2.1 Take 10 parts of styrene acrylic emulsion and 10 parts of epoxy resin by weight and place them in different containers;

[0107] S2.2 Heat the epoxy resin to 60-70°C to reduce its viscosity and facilitate mixing;

[0108] S2.3 Slowly add the heated epoxy resin into the styrene acrylic emulsion while stirring continuously to ensure that the two are evenly mixed;

[0109] S2.4 Continue stirring for 30 minutes to ensure that the mixture is evenly distributed;

[0110] S2.5 allowing the mixed packaging material to stand and cool at room temperature to obtain a final packaging material;

[0111] S2.6 Store packaging materials in airtight containers to protect them from air and moisture.

[0112] First, take 10 parts of styrene acrylic emulsion and epoxy resin by weight and place them in different containers. Then, heat the epoxy resin to 60-70°C to reduce its viscosity for subsequent mixing operations. Next, slowly add the heated epoxy resin to the styrene acrylic emulsion while stirring continuously to ensure that the two are evenly mixed. Continue stirring for 30 minutes to ensure that the mixture is evenly distributed. Finally, let the mixed encapsulation material stand and cool at room temperature to obtain the final encapsulation material, which is stored in a sealed container to avoid the influence of air and moisture, which can improve the durability and stability of the encapsulation material.

[0113] The S3 molding and curing step also includes the following specific steps:

[0114] S3.1 Mix styrene acrylic emulsion and epoxy resin in proportion to form a packaging material;

[0115] S3.2 Encapsulating the ceramsite and expanded perlite adsorbed with the phase change material with an encapsulation material to form composite phase change material particles;

[0116] S3.3 Add the composite phase change material particles into common building materials, mix them evenly, and prepare phase change energy storage mortar or phase change concrete;

[0117] S3.4 Pour the mixed building materials into a mold, shape and solidify them to obtain the final phase change energy storage building materials.

[0118] First, styrene acrylic emulsion and epoxy resin are mixed in proportion to form an encapsulation material. Then, the ceramsite and expanded perlite adsorbed with the phase change material are encapsulated with the encapsulation material to form composite phase change material particles. Next, the composite phase change material particles are added to ordinary building materials, mixed evenly, and prepared into phase change energy storage mortar or phase change concrete. Finally, the mixed building materials are poured into the mold, formed, and cured in an environment with a controlled temperature of 25-35°C for 24-48 hours to ensure the stability and performance of the material. This series of operating steps ensures that the final phase change energy storage building materials have good physical and chemical properties and are suitable for actual construction applications.

[0119] The paraffin-based phase-change energy storage building material of the present invention adjusts the internal temperature of the building by utilizing the heat absorption and heat release characteristics of organic paraffin during the phase change process. When the ambient temperature rises to the melting point of paraffin, the paraffin absorbs heat and melts, thereby lowering the temperature of the surrounding environment. When the ambient temperature drops to the solidification point of paraffin, the paraffin releases heat and solidifies, thereby increasing the temperature of the surrounding environment. In this way, the paraffin-based phase-change energy storage building material can effectively adjust the indoor temperature, reduce the energy consumption of air conditioning and heating systems, and improve the energy efficiency of buildings.

[0120] An application of a paraffin-based phase change energy storage building material comprises the following steps:

[0121] a) uniformly adding the prepared paraffin-based phase change energy storage building material into building mortar or concrete to ensure uniform distribution of the material;

[0122] b) Pour the mixed mortar or concrete into the prepared mold and shape it as required;

[0123] c) Carry out preliminary curing on the formed building materials, control the temperature at 25-35°C, and the curing time is 24-48 hours to ensure the initial hardening and stable performance of the materials;

[0124] d) The building materials after the initial curing are removed from the mold and subjected to secondary curing in an environment with controlled temperature and humidity for 7-14 days to ensure the final performance of the materials;

[0125] e) Apply the well-maintained phase change energy storage building materials to building structures, and use their energy storage characteristics to improve the thermal environment and energy efficiency of the building.

[0126] This application method describes in detail how to apply the prepared paraffin-based phase change energy storage building materials to building structures to exert their energy storage properties and improve the thermal environment and energy efficiency of the building.

[0127] a) Material mixing:

[0128] First, the prepared paraffin-based phase change energy storage building materials are evenly mixed into the mortar or concrete used for construction. This step is critical because the evenly distributed materials ensure that the entire building structure has consistent performance in terms of temperature regulation and thermal energy storage. This requires careful stirring during the mixing process to ensure the uniform distribution of the paraffin-based phase change energy storage materials in the mortar or concrete.

[0129] b) Molding:

[0130] Next, the mixed mortar or concrete is poured into a pre-prepared mold and shaped as required. The shape and size of the mold are selected according to the specific building needs. The molding process needs to ensure that the material fills all parts of the mold and avoids voids or uneven areas, thereby ensuring the structural integrity and performance consistency of the finished product.

[0131] c) Initial maintenance:

[0132] The initial curing is carried out on the formed building materials. This step is carried out in an environment with a controlled temperature of 25-35°C and the curing time is 24-48 hours. The purpose of the initial curing is to initially harden the material and ensure that it has basic mechanical properties and stability. During this period, it is necessary to maintain a suitable temperature to promote uniform hardening and performance improvement of the material.

[0133] d) Secondary maintenance:

[0134] After the initial curing, the building material is removed from the mold and subjected to secondary curing. This is carried out in an environment with controlled temperature and humidity, and the curing time is 7-14 days. The purpose of secondary curing is to further enhance the final performance of the material and ensure its durability and stability in practical applications. During this period, the temperature and humidity of the curing environment need to be regularly checked and adjusted to ensure that the material completes the hardening process under optimal conditions.

[0135] e) Applied to building structures:

[0136] Finally, the well-maintained phase change energy storage building materials are applied to building structures, such as walls, roofs and floors. By utilizing its energy storage characteristics, the materials can absorb and store solar heat during the day and release heat at night, thereby regulating indoor temperature, reducing the frequency of use of air conditioning and heating systems, and improving the energy efficiency and living comfort of buildings.

[0137] The paraffin-based phase-change energy storage building material of the present invention exerts its energy storage characteristics by achieving temperature regulation in the building structure. During the day, the material absorbs heat from the environment, melts the paraffin and stores heat; at night or when the temperature drops, the material releases the stored heat, solidifies the paraffin, and thus provides heat for the interior of the building. This process is repeated to regulate the temperature fluctuations inside the building and improve energy utilization efficiency.

[0138] Example 1: Application of paraffin-based phase change energy storage building materials in residential building walls

[0139] This example aims to verify the application effect of paraffin-based phase change energy storage building materials in residential building walls. Traditional building materials have limited effect in regulating indoor temperature, while the paraffin-based phase change energy storage building materials of the present invention can significantly improve the energy efficiency of buildings by absorbing and releasing heat, reduce the frequency of use of air conditioning and heating systems, thereby reducing energy consumption and improving living comfort.

[0140] The innovation of this embodiment is to utilize the high-efficiency heat storage and heat release characteristics of paraffin-based phase change energy storage materials, combined with porous matrix materials and packaging materials, to form a composite material suitable for residential building walls. The material absorbs heat during the day and releases heat at night, effectively regulating indoor temperature, and is particularly suitable for areas with large temperature differences between summer and winter.

[0141] After applying paraffin-based phase change energy storage materials in the walls of residential buildings, comparative experiments have shown that this material has significant advantages in temperature regulation, energy consumption reduction and living comfort.

[0142] Comparative experiment

[0143] The comparative experiment selected two groups of samples for testing:

[0144] Traditional building material walls;

[0145] Paraffin-based phase change energy storage building material wall.

[0146] Experimental variables:

[0147] Type of wall material;

[0148] Ambient temperature changes;

[0149] Energy consumption (air conditioning and heating system usage).

[0150] Experimental results:

[0151]

[0152]

[0153] Example 2: Application of paraffin-based phase change energy storage building materials in office building roofs

[0154] This example is intended to verify the application effect of paraffin-based phase change energy storage building materials in the roof of an office building. Office buildings usually have large glass windows and roofs directly exposed to the sun, and the indoor temperature fluctuates greatly, resulting in high-frequency use of air conditioning and heating systems. The paraffin-based phase change energy storage building materials of the present invention can effectively alleviate this problem by absorbing and releasing heat from the roof.

[0155] The innovation of this embodiment is to utilize the high-efficiency heat storage and heat release characteristics of paraffin-based phase change energy storage materials, combined with porous matrix materials and packaging materials, to form a composite material suitable for office building roofs. This material absorbs solar heat during the day and releases heat at night, effectively regulating indoor temperature, and is particularly suitable for large-area roofs and high-rise buildings.

[0156] After applying paraffin-based phase change energy storage materials on the roof of an office building, comparative experiments showed that the material has significant advantages in temperature regulation, energy consumption reduction and office environment comfort.

[0157] Comparative experiment

[0158] The comparative experiment selected two groups of samples for testing:

[0159] Traditional building materials roof

[0160] Paraffin-based phase change energy storage building material roof

[0161] Experimental variables:

[0162] Roofing Material Types

[0163] Ambient temperature changes

[0164] Energy consumption (air conditioning and heating system usage)

[0165] Experimental results:

[0166]

[0167] Through the detailed comparative experiments of the above two embodiments, it can be clearly seen that the paraffin-based phase change energy storage building material of the present invention has shown significant advantages in different application scenarios. Specifically, it is embodied in:

[0168] The indoor temperature fluctuation range is significantly reduced: Compared with traditional building materials, paraffin-based phase change energy storage materials can better regulate indoor temperature and reduce temperature fluctuations.

[0169] Energy consumption is significantly reduced: the use time of air conditioning and heating systems is greatly reduced, which significantly reduces electricity bills.

[0170] Improved comfort of living and working environment: Thanks to the stable indoor temperature, the comfort score of living and working environment has been greatly improved.

[0171] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A paraffin-based phase change energy storage building material, composed of composite phase change material particles, characterized by: The material consists of the following components: Phase change material group: organic paraffin, stearic acid, polyethylene glycol (PEG 1000); Porous matrix material group: ceramsite, expanded perlite, expanded clay materials; Packaging material group: styrene acrylic emulsion, epoxy resin.

2. The paraffin-based phase change energy storage building material according to claim 1, characterized in that: The paraffin-based phase change energy storage building material includes the following specific components: Organic paraffin: 30-50 parts; Stearic acid: 10-20 parts; Polyethylene glycol (PEG 1000): 10-20 parts; Ceramic granules: 10-30 parts; Expanded perlite: 10-30 parts; Expanded clay material: 10-20 parts; Styrene acrylic emulsion: 5-15 parts; Epoxy resin: 5-15 parts.

3. The paraffin-based phase change energy storage building material according to claim 2, characterized in that: The specific composition of the paraffin-based phase change energy storage building material is: Organic paraffin: 40 parts; Stearic acid: 15 parts; Polyethylene glycol (PEG 1000): 15 parts; Ceramic granules: 20 parts; Expanded perlite: 20 parts; Expanded clay material: 15 parts; Styrene acrylic emulsion: 10 parts; Epoxy resin: 10 parts.

4. The paraffin-based phase change energy storage building material according to claim 3, characterized in that: The particle size range of the ceramsite and expanded perlite is 1-5 mm; The encapsulated composite phase change material particles have a specific surface area of ​​20-40m 2 / g; The thermal conductivity of the composite phase change material particles is 0.5-1.5 W / (m·K) in the range of 20-30°C; The heat-resistant temperature of the packaging material group is 70-90°C.

5. A method for preparing a paraffin-based phase-change energy storage building material, applied to a paraffin-based phase-change energy storage building material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Raw material preparation: a) heating organic paraffin, stearic acid, and polyethylene glycol (PEG 1000) to 60-80° C. under stirring until completely mixed to form a uniform liquid composite material; b) drying the ceramsite, expanded perlite and expanded clay materials at a drying temperature of 100-120° C. for 1-2 hours to reduce the moisture content; S2. Material mixing: a) mixing the pretreated liquid composite material with the dried ceramsite, expanded perlite and expanded clay material in the proportions described above to ensure uniform distribution of the components; b) During the mixing process, gradually add the styrene acrylic emulsion and epoxy resin and continue stirring for 15-20 minutes to ensure that the mixture is uniform; S3, molding and curing: a) pouring the mixed material into a mold for molding; b) Curing in a controlled temperature environment of 25-35°C for 24-48 hours to ensure the stability and performance of the material.

6. The method for preparing a paraffin-based phase change energy storage building material according to claim 5, characterized in that: The S1 raw material preparation step also includes the following specific steps: S1.1 Mix organic paraffin, stearic acid, and polyethylene glycol (PEG 1000) in appropriate proportions and heat until completely melted to form a uniform phase change material mixture; S1.2 Pre-treat the ceramsite and expanded perlite to ensure they are clean and dry; S1.3 Use vacuum adsorption to adsorb the phase change material mixture into the interior of the ceramsite and expanded perlite.

7. The method for preparing a paraffin-based phase-change energy storage building material according to claim 5, characterized in that: The S2 material mixing step further includes the following specific steps: S2.1 Take 10 parts of styrene acrylic emulsion and 10 parts of epoxy resin by weight and place them in different containers; S2.2 Heat the epoxy resin to 60-70°C to reduce its viscosity and facilitate mixing; S2.3 Slowly add the heated epoxy resin to the styrene acrylic emulsion while stirring continuously to ensure that the two are evenly mixed; S2.4 Continue stirring for 30 minutes to ensure that the mixture is evenly distributed; S2.5 allowing the mixed packaging material to cool at room temperature to obtain the final packaging material; S2.6 Store packaging materials in sealed containers to protect them from air and moisture.

8. The method for preparing a paraffin-based phase-change energy storage building material according to claim 5, characterized in that: The S3 molding and curing step also includes the following specific steps: S3.1 Mix styrene acrylic emulsion and epoxy resin in proportion to form a packaging material; S3.2 Encapsulating the ceramsite and expanded perlite adsorbed with the phase change material with an encapsulation material to form composite phase change material particles; S3.3 Add the composite phase change material particles to ordinary building materials, mix them evenly, and prepare phase change energy storage mortar or phase change concrete; S3.4 Pour the mixed building materials into a mold, shape and solidify them to obtain the final phase change energy storage building materials.

9. A use of the paraffin-based phase change energy storage building material according to any one of claims 1 to 4, characterized in that: The method of applying the paraffin-based phase change energy storage building material obtained by the preparation method of the paraffin-based phase change energy storage building material according to any one of claims 5 to 8 to a building structure comprises the following steps: a) evenly adding the prepared paraffin-based phase change energy storage building material into building mortar or concrete to ensure uniform distribution of the material; b) Pour the mixed mortar or concrete into the prepared mold and shape it as required; c) Carry out preliminary curing on the formed building materials, controlling the temperature at 25-35°C and the curing time for 24-48 hours to ensure the initial hardening and stable performance of the materials; d) After the initial curing, the building material is removed from the mold and subjected to secondary curing in an environment with controlled temperature and humidity for 7-14 days to ensure the final performance of the material; e) Apply the well-maintained phase change energy storage building materials to building structures, and utilize their energy storage properties to improve the thermal environment and energy efficiency of the building.